Use of Frontal Sinus Morphometric Analysis by Computerized Tomography in Sex Determination - Ekizoğlu, Oğuzhan; Hocaoğlu, Elif; İnci, Ercan (The Bulletin of Legal Medicine, 2017)
AbstractObjective:  The aim of the this study is to evaluate usefulness of results of measurements via computerized tomography of frontal sinus dimensions in sex determination.Materials and methods: In Bakirkoy Training and Research Hospital subjects who had performed maxillofacial computed tomography were included. Transvers diameters (width) were measured from axial images, anterior-posterior (depth) and cephalo-caudal diameters (height) were measured from sagittal reformatted images. Measurements were performed for both left and right frontal sinuses. The size of frontal sinuses on both sides were obtained using these parameters. These values were evaluated with independent t test .The variables were evaluated discrimination function analysisResults: For study 400 subjects were evaluated (200 male and 200 female). 400 case (female/male: 200/200, mean age: 30.12 ± 10.2)   All values for left and right transvers, cephalo-caudal and antero-posterior measurements showed significant difference between sex. Male sex had significant increased valued then female sex.  (p
Keywords: frontal sinus; sex determinatio; sex determination; computerized tomography